Internal structure of the fly elementary motion detector - Eichner, Hubert; Maximilian Jösch; Schnell, Bettina; Reiff, Dierk F; Borst, Alexander (Neuron)
Recent experiments have shown that motion detection in Drosophila starts with splitting the visual input into two parallel channels encoding brightness increments (ON) or decrements (OFF). This suggests the existence of either two (ON-ON, OFF-OFF) or four (for all pairwise interactions) separate motion detectors. To decide between these possibilities, we stimulated flies using sequences of ON and OFF brightness pulses while recording from motion-sensitive tangential cells. We found direction-selective responses to sequences of same sign (ON-ON, OFF-OFF), but not of opposite sign (ON-OFF, OFF-ON), refuting the existence of four separate detectors. Based on further measurements, we propose a model that reproduces a variety of additional experimental data sets, including ones that were previously interpreted as support for four separate detectors. Our experiments and the derived model mark an important step in guiding further dissection of the fly motion detection circuit.

Min protein patterns emerge from rapid rebinding and membrane interaction of MinE - Martin Loose; Fischer-Friedrich, Elisabeth; Herold, Christoph; Kruse, Karsten; Schwille, Petra (Nature Structural and Molecular Biology)
In Escherichia coli, the pole-to-pole oscillation of the Min proteins directs septum formation to midcell, which is required for symmetric cell division. In vitro, protein waves emerge from the self-organization of MinD, a membrane-binding ATPase, and its activator MinE. For wave propagation, the proteins need to cycle through states of collective membrane binding and unbinding. Although MinD presumably undergoes cooperative membrane attachment, it is unclear how synchronous detachment is coordinated. We used confocal and single-molecule microscopy to elucidate the order of events during Min wave propagation. We propose that protein detachment at the rear of the wave, and the formation of the E-ring, are accomplished by two complementary processes: first, local accumulation of MinE due to rapid rebinding, leading to dynamic instability; and second, a structural change induced by membrane-interaction of MinE in an equimolar MinD-MinE (MinDE) complex, which supports the robustness of pattern formation.

Protein self-organization: Lessons from the min system - Martin Loose; Kruse, Karsten; Schwille, Petra (Annual Review of Biophysics)
One of the most fundamental features of biological systems is probably their ability to self-organize in space and time on different scales. Despite many elaborate theoretical models of how molecular self-organization can come about, only a few experimental systems of biological origin have so far been rigorously described, due mostly to their inherent complexity. The most promising strategy of modern biophysics is thus to identify minimal biological systems showing self-organized emergent behavior. One of the best-understood examples of protein self-organization, which has recently been successfully reconstituted in vitro, is represented by the oscillations of the Min proteins in Escherichia coli. In this review, we summarize the current understanding of the mechanism of Min protein self-organization in vivo and in vitro. We discuss the potential of the Min oscillations to sense the geometry of the cell and suggest that spontaneous protein waves could be a general means of intracellular organization. We hypothesize that cooperative membrane binding and unbinding, e.g., as an energy-dependent switch, may act as an important regulatory mechanism for protein oscillations and pattern formation in the cell.

Lack of global dosage compensation in Schistosoma mansoni, a female-heterogametic parasite - Vicoso, Beatriz; Bachtrog, Doris (Genome Biology and Evolution)
Many species have morphologically and genetically differentiated sex chromosomes, such as the XY pair of mammals. Y chromosomes are often highly degenerated and carry few functional genes, so that XY males have only one copy of most Xlinked genes (whereas females have two). As a result, chromosome-wide mechanisms of dosage compensation, such as the mammalian X-inactivation, often evolve to reestablish expression balance. A similar phenomenon is expected in femaleheterogametic species, where ZW females should suffer from imbalances due to W-chromosome degeneration. However, no global dosage compensation mechanisms have been detected in the two independent ZW systems that have been studied systematically (birds and silkworm), leading to the suggestion that lack of global dosage compensation may be a general feature of female-heterogametic species. However, analyses of other independently evolved ZW systems are required to test if this is the case. In this study, we use published genomic and expression data to test for the presence of global dosage compensation in Schistosoma mansoni, a trematode parasite that causes schistosomiasis in humans. We find that Z-linked expression is reduced relative to autosomal expression in females but not males, consistent with incomplete or localized dosage compensation. This gives further support to the theory that female-heterogametic species may not require global mechanisms of dosage compensation.

Structure of the membrane domain of respiratory complex i - Efremov, Rouslan G; Leonid Sazanov (Nature)
Complex I is the first and largest enzyme of the respiratory chain, coupling electron transfer between NADH and ubiquinone to the translocation of four protons across the membrane. It has a central role in cellular energy production and has been implicated in many human neurodegenerative diseases. The L-shaped enzyme consists of hydrophilic and membrane domains. Previously, we determined the structure of the hydrophilic domain. Here we report the crystal structure of the Esherichia coli complex I membrane domain at 3.0 Ã. resolution. It includes six subunits, NuoL, NuoM, NuoN, NuoA, NuoJ and NuoK, with 55 transmembrane helices. The fold of the homologous antiporter-like subunits L, M and N is novel, with two inverted structural repeats of five transmembrane helices arranged, unusually, face-to-back. Each repeat includes a discontinuous transmembrane helix and forms half of a channel across the membrane. A network of conserved polar residues connects the two half-channels, completing the proton translocation pathway. Unexpectedly, lysines rather than carboxylate residues act as the main elements of the proton pump in these subunits. The fourth probable proton-translocation channel is at the interface of subunits N, K, J and A. The structure indicates that proton translocation in complex I, uniquely, involves coordinated conformational changes in six symmetrical structural elements.

Respiratory complex I: 'steam engine' of the cell? - Efremov, Rouslan G; Leonid Sazanov (Current Opinion in Structural Biology)
Complex I is the first enzyme of the respiratory chain and plays a central role in cellular energy production. It has been implicated in many human neurodegenerative diseases, as well as in ageing. One of the biggest membrane protein complexes, it is an L-shaped assembly consisting of hydrophilic and membrane domains. Previously, we have determined structures of the hydrophilic domain in several redox states. Last year was marked by fascinating breakthroughs in the understanding of the complete structure. We described the architecture of the membrane domain and of the entire bacterial complex I. X-ray analysis of the larger mitochondrial enzyme has also been published. The core subunits of the bacterial and mitochondrial enzymes have remarkably similar structures. The proposed mechanism of coupling between electron transfer and proton translocation involves long-range conformational changes, coordinated in part by a long α-helix, akin to the coupling rod of a steam engine.

Evolution of respiratory complex I "Supernumerary" subunits are present in the α-proteobacterial enzyme - Yip, Chui Y; Harbour, Michael E; Jayawardena, Kamburapola G; Fearnley, Ian M; Leonid Sazanov (Journal of Biological Chemistry)
Modern α-proteobacteria are thought to be closely related to the ancient symbiont of eukaryotes, an ancestor of mitochondria. Respiratory complex I from α-proteobacteria and mitochondria is well conserved at the level of the 14 "core" subunits, consistent with that notion. Mitochondrial complex I contains the core subunits, present in all species, and up to 31 "supernumerary" subunits, generally thought to have originated only within eukaryotic lineages. However, the full protein composition of an α-proteobacterial complex I has not been established previously. Here, we report the first purification and characterization of complex I from the α-proteobacterium Paracoccus denitrificans. Single particle electron microscopy shows that the complex has a well defined L-shape. Unexpectedly, in addition to the 14 core subunits, the enzyme also contains homologues of three supernumerary mitochondrial subunits as follows: B17.2, AQDQ/18, and 13 kDa (bovine nomenclature). This finding suggests that evolution of complex I via addition of supernumerary or "accessory" subunits started before the original endosymbiotic event that led to the creation of the eukaryotic cell. It also provides further confirmation that α-proteobacteria are the closest extant relatives of mitochondria.

Spatio-temporal extraction of articulated models in a graph pyramid - Artner, Nicole M.; Ion, Adrian; Kropatsch, Walter G. (Graph-Based Representations in Pattern Recognition)
This paper presents a method to create a model of an articulated object using the planar motion in an initialization video. The model consists of rigid parts connected by points of articulation. The rigid parts are described by the positions of salient feature-points tracked throughout the video. Following a filtering step that identifies points that belong to different objects, rigid parts are found by a grouping process in a graph pyramid. Valid articulation points are selected by verifying multiple hypotheses for each pair of parts.

Droplet and cluster formation in freely falling granular streams - Waitukaitis, Scott R; Grütjen, Helge; Royer, John; Jaeger, Heinrich (Physical Review E)
Particle beams are important tools for probing atomic and molecular interactions. Here we demonstrate that particle beams also offer a unique opportunity to investigate interactions in macroscopic systems, such as granular media. Motivated by recent experiments on streams of grains that exhibit liquid-like breakup into droplets, we use molecular dynamics simulations to investigate the evolution of a dense stream of macroscopic spheres accelerating out of an opening at the bottom of a reservoir. We show how nanoscale details associated with energy dissipation during collisions modify the stream\'s macroscopic behavior. We find that inelastic collisions collimate the stream, while the presence of short-range attractive interactions drives structure formation. Parameterizing the collision dynamics by the coefficient of restitution (i.e., the ratio of relative velocities before and after impact) and the strength of the cohesive interaction, we map out a spectrum of behaviors that ranges from gaslike jets in which all grains drift apart to liquid-like streams that break into large droplets containing hundreds of grains. We also find a new, intermediate regime in which small aggregates form by capture from the gas phase, similar to what can be observed in molecular beams. Our results show that nearly all aspects of stream behavior are closely related to the velocity gradient associated with vertical free fall. Led by this observation, we propose a simple energy balance model to explain the droplet formation process. The qualitative as well as many quantitative features of the simulations and the model compare well with available experimental data and provide a first quantitative measure of the role of attractions in freely cooling granular streams.

Ultracold and dense samples of ground-state molecules in lattice potentials - Nägerl, Hanns; Mark, Manfred; Haller, Elmar; Gustavsson, Mattias; Hart, Russell; Danzl, Johann G (Journal of Physics: Conference Series)
We produce an ultracold and dense sample of rovibronic ground state Cs 2 molecules close to the regime of quantum degeneracy, in a single hyperfine level, in the presence of an optical lattice. The molecules are individually trapped, in the motional ground state of an optical lattice well, with a lifetime of 8 s. For preparation, we start with a zero-temperature atomic Mott-insulator state with optimized double-site occupancy and efficiently associate weakly-bound dimer molecules on a Feshbach resonance. Despite extremely weak Franck-Condon wavefunction overlap, the molecules are subsequently transferred with >50% efficiency to the rovibronic ground state by a stimulated four-photon process. Our results present a crucial step towards the generation of Bose-Einstein condensates of ground-state molecules and, when suitably generalized to polar heteronuclear molecules such as RbCs, the realization of dipolar many-body quantum-gas phases in periodic potentials.

Global analysis of data on the spin-orbit-coupled A 1Σu+ and b 3Πu inf states of Cs2 - Bai, Jianmei; Ahmed, Ergin; Beser, Bediha; Guan, Yafei; Kotochigova, Svetlana; Lyyra, Marjatta; Ashman, Seth; Wolfe, Christopher; Huennekens, John; Xie, Feng; Li, Dan; Li, Li; et al. (Physical Review A - Atomic, Molecular, and Optical Physics)
We present experimentally derived potential curves 1?and spin-orbit interaction functions for the strongly perturbed AΣu+ 3?and bΠu states of the cesium dimer. The results are based on data from several sources. Laser-induced fluorescence Fourier transform spectroscopy (LIF FTS) was used some time ago in the Laboratoire Aimé Cotton primarily to study the XΣg+ state. More recent work at Tsinghua University provides information from moderate 3?resolution spectroscopy on the lowest levels of the bΠ0u± state as well as additional high-resolution data. From Innsbruck University, we have precision data obtained with cold Cs2 molecules. Recent data from Temple University was obtained using the optical-optical double resonance polarization spectroscopy technique, and finally, a group at the University of Latvia has added additional LIF FTS data. In the Hamiltonian matrix, we have used analytic potentials (the expanded Morse oscillator form) with both finite-difference (FD) coupled-channel and discrete variable representation (DVR) calculations of the term values. Fitted diagonal and off-diagonal spin-orbit functions are obtained and compared with ab initio results from Temple and Moscow State universities.

Demonstration of the temporal matter-wave Talbot effect for trapped matter waves - Mark, Manfred; Haller, Elmar; Danzl, Johann G; Lauber, Katharina; Gustavsson, Mattias; Nägerl, Hanns (New Journal of Physics)
We demonstrate the temporal Talbot effect for trapped matter waves using ultracold atoms in an optical lattice. We investigate the phase evolution of an array of essentially non-interacting matter waves and observe matter-wave collapse and revival in the form of a Talbot interference pattern. By using long expansion times, we image momentum space with sub-recoil resolution, allowing us to observe fractional Talbot fringes up to tenth order.

Optimal trapping wavelengths of Cs 2 molecules in an optical lattice - Vexiau, Romain; Bouloufa, Nadia; Aymar, Mireille; Danzl, Johann G; Mark, Manfred; Nägerl, Hanns; Dulieu, Olivier (European Physical Journal D)
The present paper aims at finding optimal parameters for trapping of Cs 2 molecules in optical lattices, with the perspective of creating a quantum degenerate gas of ground-state molecules. We have calculated dynamic polarizabilities of Cs 2 molecules subject to an oscillating electric field, using accurate potential curves and electronic transition dipole moments. We show that for some particular wavelengths of the optical lattice, called "magic wavelengths", the polarizability of the ground-state molecules is equal to the one of a Feshbach molecule. As the creation of the sample of ground-state molecules relies on an adiabatic population transfer from weakly-bound molecules created on a Feshbach resonance, such a coincidence ensures that both the initial and final states are favorably trapped by the lattice light, allowing optimized transfer in agreement with the experimental observation.

Precision measurements on a tunable Mott insulator of ultracold atoms - Mark, Manfred; Haller, Elmar; Lauber, Katharina; Danzl, Johann G; Daley, Andrew; Nägerl, Hanns (Physical Review Letters)
We perform precision measurements on a Mott-insulator quantum state of ultracold atoms with tunable interactions. We probe the dependence of the superfluid-to-Mott-insulator transition on the interaction strength and explore the limits of the standard Bose-Hubbard model description. By tuning the on-site interaction energies to values comparable to the interband separation, we are able to quantitatively measure number-dependent shifts in the excitation spectrum caused by effective multibody interactions.

Three-body correlation functions and recombination rates for bosons in three dimensions and one dimension - Haller, Elmar; Rabie, Mahmoud; Mark, Manfred; Danzl, Johann G; Hart, Russell; Lauber, Katharina; Pupillo, Guido; Nägerl, Hanns (Physical Review Letters)
We investigate local three-body correlations for bosonic particles in three dimensions and one dimension as a function of the interaction strength. The three-body correlation function g(3) is determined by measuring the three-body recombination rate in an ultracold gas of Cs atoms. In three dimensions, we measure the dependence of g(3) on the gas parameter in a BEC, finding good agreement with the theoretical prediction accounting for beyond-mean-field effects. In one dimension, we observe a reduction of g( 3) by several orders of magnitude upon increasing interactions from the weakly interacting BEC to the strongly interacting Tonks-Girardeau regime, in good agreement with predictions from the Lieb-Liniger model for all strengths of interaction.

From sparse mocap to highly detailed facial animation - Bernd Bickel; Lang, Manuel (GPU Computing Gems Emerald Edition)
This chapter presents a method for real-time animation of highly detailed facial expressions based on sparse motion captures data and a limited set of static example poses. The method for real-time animation of highly detailed facial expressions decomposes geometry into large-scale motion and fine-scale details, such as expression wrinkles. Both large- and fine-scale deformation algorithms run entirely on the GPU, and our implementation based on CUDA achieves an overall performance of about 30 fps. The face conveys the most relevant visual characteristics of human identity and expression. Hence, realistic facial animations or interactions with virtual avatars are important for storytelling and gameplay. However, current approaches are either computationally expensive, require very specialized capture hardware, or are extremely labor intensive. At runtime, given an arbitrary facial expression, the algorithm computes the skin strain from the relative distance between marker points and derives fine-scale corrections for the largescale deformation. During gameplay only the sparse set of marker-point positions is transmitted to the GPU. The face animation is entirely computed on the GPU where the resulting mesh can directly be used as input for the rendering stages. This data can be easily obtained by traditional capture hardware. The proposed in-game algorithm is fast. It also is easy to implement and maps well onto programmable GPUs.

High-quality passive facial performance capture using anchor frames - Beeler, Thabo; Hahn, Fabian; Bradley, Derek J; Bernd Bickel; Beardsley, Paul A; Gotsman, Craig; Sumner, Robert W; Groß, Markus S (ACM Transactions on Graphics)
We present a new technique for passive and markerless facial performance capture based on anchor frames. Our method starts with high resolution per-frame geometry acquisition using state-of-theart stereo reconstruction, and proceeds to establish a single triangle mesh that is propagated through the entire performance. Leveraging the fact that facial performances often contain repetitive subsequences, we identify anchor frames as those which contain similar facial expressions to a manually chosen reference expression. Anchor frames are automatically computed over one or even multiple performances. We introduce a robust image-space tracking method that computes pixel matches directly from the reference frame to all anchor frames, and thereby to the remaining frames in the sequence via sequential matching. This allows us to propagate one reconstructed frame to an entire sequence in parallel, in contrast to previous sequential methods. Our anchored reconstruction approach also limits tracker drift and robustly handles occlusions and motion blur. The parallel tracking and mesh propagation offer low computation times. Our technique will even automatically match anchor frames across different sequences captured on different occasions, propagating a single mesh to all performances.

Throwable panoramic ball camera - Pfeil, Jonas; Hildebrand, Kristian; Gremzow, Carsten; Bernd Bickel; Alexa, Marc
Acquiring panoramic images using stitching takes a lot of time and moving objects may cause ghosting. It is also difficult to obtain a full spherical panorama, because the downward picture cannot be captured while the camera is mounted on the tripod.

Gradient estimates and domain identification for analytic Ornstein-Uhlenbeck operators - Jan Maas; Van Neerven, Jan (Parabolic Problems)
Let P be the Ornstein-Uhlenbeck semigroup associated with the stochastic Cauchy problem dU(t)=AU(t)dt+dWH(t), where A is the generator of a C 0-semigroup S on a Banach space E, H is a Hilbert subspace of E, and W H is an H-cylindrical Brownian motion. Assuming that S restricts to a C 0-semigroup on H, we obtain L p -bounds for D H P(t). We show that if P is analytic, then the invariance assumption is fulfilled. As an application we determine the L p -domain of the generator of P explicitly in the case where S restricts to a C 0-semigroup on H which is similar to an analytic contraction semigroup. The results are applied to the 1D stochastic heat equation driven by additive space-time white noise.

Conical square functions and non-tangential maximal functions with respect to the Gaussian measure - Jan Maas; van Neerven, Jan M; Portal, Pierre (Publicacions Matemàtiques)
We study, in L1(R̃n; γ) with respect to the gaussian measure, non- tangential maximal functions and conical square functions associ- ated with the Ornstein-Uhlenbeck operator by developing a set of techniques which allow us, to some extent, to compensate for the non-doubling character of the gaussian measure. The main result asserts that conical square functions can be controlled in L1-norm by non-tangential maximal functions. Along the way we prove a change of aperture result for the latter. This complements recent results on gaussian Hardy spaces due to Mauceri and Meda.